1989
DOI: 10.1111/j.1600-0714.1989.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Sialochemistry in Sjögren's syndrome: a review

Abstract: Sjögren's syndrome (SS) is an autoimmune exocrinopathy. The salivary glands are the site of activated T- and B-lymphocytes, along with gradual parenchymal destruction, diminished flow and altered composition of the secretory product. At present, sialochemistry has achieved no significance for the evaluation of SS patient. However, the number of sialochemical publications is steadily growing. This study review current sialochemical findings in patients with SS and relate the observations to the present concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 115 publications
(88 reference statements)
1
19
0
Order By: Relevance
“…The presence of these two phenomena leads to a diagnosis of primary SS. In secondary SS, a well-defined connective tissue disease (most commonly rheumatoid arthritis or systemic lupus erythematosus) is present in addition to the xerostomia and/or the keratoconjunctivitis (Schiødt and Thorn, 1989;Thorn et al ., 1989). In addition to involvement of the salivary and lacrimal glands, SS may also affect the skin, lungs, liver, kidneys, thyroid, and nervous system (Talal, 1992).…”
Section: Autoimmunediseases -S Jögren ' S Syndromementioning
confidence: 99%
“…The presence of these two phenomena leads to a diagnosis of primary SS. In secondary SS, a well-defined connective tissue disease (most commonly rheumatoid arthritis or systemic lupus erythematosus) is present in addition to the xerostomia and/or the keratoconjunctivitis (Schiødt and Thorn, 1989;Thorn et al ., 1989). In addition to involvement of the salivary and lacrimal glands, SS may also affect the skin, lungs, liver, kidneys, thyroid, and nervous system (Talal, 1992).…”
Section: Autoimmunediseases -S Jögren ' S Syndromementioning
confidence: 99%
“…Neither the concentration nor the output of total protein in stimulated parotid saliva were significantly different in the patients with secondary Sjögren©s syndrome compared to the normal controls. A review of eight studies of parotid salivary protein secretion by Thorn et al [23] revealed that compared to healthy controls, Sjögren©s syndrome protein concentration can be increased (two studies), decreased (one study) or remain unchanged (five studies). In our examination of protein composition in the different subject groups there was great variation in protein banding patterns between subjects, as revealed by FITC staining of nitrocellulose blots.…”
Section: Discussionmentioning
confidence: 97%
“…Determination of [32-m, LZM and Lf in saliva has frequently been proposed for diagnostic use in primary SS but so far insufficient data have prevented its clinical use (11)(12)(13)(14)(19)(20)(21). To our knowledge this is the first study to establish simultaneously the diagnostic value of salivary fluid levels of [32-m, LZM and Lf for primary SS.…”
Section: Discussionmentioning
confidence: 99%
“…of 132-microglobulin (132-m), lysozyme (LZM), and lactoferrin (Lf) has been proposed for this goal (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%